The nuclear envelope can control gene expression and cell cycle progression via miRNA regulation. - Malhas, A; Saunders, N; Vaux, D (2010)
The nuclear envelope can regulate gene expression through its interaction with chromatin and by the sequestration of specific transcription factors. In this study, we show that such regulation can be achieved via microRNA regulation. We identify a set of miRNAs that are dysregulated in the absence of a fully functional nuclear lamina. We then focus on miRNA-31 and experimentally confirm its targets. The target set identified is significantly enriched in genes involved in controlling progress through the cell cycle such as Cdkn2a. Normalizing miRNA-31 levels, either using a specific inhibitor or by restoration of the nuclear lamina, also normalizes cell cycle distribution and cell proliferation rates. We show that the 3'UtR of p16(Ink4a)/p19(Arf) has a functional miRNA-31 binding site which contributes to the observed regulation of cell cycle progression. Our findings are the first demonstration that the nuclear envelope can control gene expression by regulating specific miRNA levels, and that miRNA-31 is involved in the regulation of cell proliferation and progress through the cell cycle at least in part by regulating the levels of p16(Ink4a)/p19(Arf).